2011
DOI: 10.1093/biolreprod/85.s1.83
|View full text |Cite
|
Sign up to set email alerts
|

Removing Seminal Plasma Improves Sex-Sorting of Bovine Sperm.

Abstract: REMOVING SEMINAL PLASMA IMPROVES SEX-SORTING OF BOVINE SPERMExperiments for this thesis evaluated how characteristics of bovine ejaculates affect efficiency of sorting X-from Y-chromosome bearing sperm by flow cytometry/cell sorting, and further, document that removal of seminal plasma improves efficacy of sexsorting bovine sperm. In Experiment I, ejaculates were collected by artificial vagina, two each from 10 bulls with an average of one hour between collections. Semen was centrifuged to separate sperm from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Maxwell et al (1996) found the presence of seminal plasma in simple sorting diluents had no effect during Hoechst staining, but reported supplementation of the collection medium to be beneficial. However, more recent studies (on high speed sorters and in more complex media) reported decreases in the number of viable and correctly orientated spermatozoa when seminal plasma (5-20% v ⁄ v) was present in the staining medium (Burroughs 2011), which caused a reduction in the speed at which spermatozoa could be sex-sorted. In addition, this detrimental effect of seminal plasma prior to sorting was evident after sorting (where membranedamaged sperm are removed) and freezing, indicating a persistent destabilization of the sperm membrane.…”
Section: Supplementation Of Seminal Plasma In the Bullmentioning
confidence: 99%
“…Maxwell et al (1996) found the presence of seminal plasma in simple sorting diluents had no effect during Hoechst staining, but reported supplementation of the collection medium to be beneficial. However, more recent studies (on high speed sorters and in more complex media) reported decreases in the number of viable and correctly orientated spermatozoa when seminal plasma (5-20% v ⁄ v) was present in the staining medium (Burroughs 2011), which caused a reduction in the speed at which spermatozoa could be sex-sorted. In addition, this detrimental effect of seminal plasma prior to sorting was evident after sorting (where membranedamaged sperm are removed) and freezing, indicating a persistent destabilization of the sperm membrane.…”
Section: Supplementation Of Seminal Plasma In the Bullmentioning
confidence: 99%